Genetic heterogeneity of proteolytic bacteria isolated from sediments mangrove areas based on repetitive sequence-based polymerase chain reaction and 16S-rRNA gene sequences - wilis ari setyati; ERNI MARTANI; TRIYANTO; MUHAMMAD ZAINUDDIN; MAYA PUSPITA; CHRISNA ADI SURYONO; SUBAGYO; delianis pringgenies (Society for Indonesian Biodiversity, 2019)
Abstract. Setyati WA, Martani E, Triyanto, Zainuddin M, Puspita M, Suryono CA, Subagyo, Pringgenies D. 2019. Genetic heterogeneity of proteolytic bacteria isolated from sediments mangrove areas based on repetitive sequence-based polymerase chain reaction and 16S-rRNA gene sequences. Biodiversitas 20: 3256-3261. Intensive shrimp farming has organic waste that results in pollution. Such waste needs to be bio-remediated for liquid waste. This study aimed to discover bacteria isolated from mangrove sediments that can degrade organic matter and apply them for bioremediation of polluted shrimp farms. The study consisted of bacterial isolation, bioassay of enzymatic activity, and isolates identification through cluster analysis. Bacterial isolates were collected from mangrove ecosystems in Rembang (R), Cilacap (C), Banyuwangi (B), and Karimunjawa (K). Enzymatic activity test consists of proteolytic, amylolytic, cellulolytic, lipolytic, and ligninolytic activity. Identification analysis was conducted with 16S-rRNA gene sequences followed by cluster analysis using the results of Rep-PCR. There were 19 isolates derived from proteolytic mangrove area represented in five clusters (groups). Group 1 consisted of 5 isolates; isolates 14.C, 22.R, 28.K, 15.C and 19.R. Group 2 consisted of 5 isolates; 30.K, 33.K, 34.K, 39.K and 40.B. Group 3 consisted of 3 isolates of bacteria; 13.C, 2.C and 32.C. Group 4 consisted of 5 isolates; isolates 36.K, 35.K, 37.K, 38.K and 48.B. Group 5 consisted of 1 isolate was isolate 26.R. The results of the sequences analysis of the 16S-rRNA gene indicated that the isolate 13C of the Group 3 had 97% sequence homology with Bacillus oceanisediminis strain H2. Isolate 14.C of the Group 1 had 96% sequence homology with Halomonas aquamarina strain DSM 30161. Isolate 26.R of the Group 5 had 98% sequence homology with Acinetobacter pitti strain ATCC 19004. Isolate 30.K of the Group 2 had 93% sequence homology with Salinicola salarius strain M27. Isolate 36.K of the Group 4 had 97% sequence homology with Bacillus aquimaris strain TF-12. Please write here your concluding remarks based on your results obtained.